2022
DOI: 10.3389/fpsyg.2022.913872
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between negative peer relationship and non-suicidal self-injury in Chinese adolescents: A moderated-mediation model

Abstract: ObjectiveThe objective of the study was to investigate the mediating effect of regulatory emotional self-efficacy (RESE) between negative peer relationship and non-suicidal self-injury (NSSI), as well as the moderating effect of gender difference.MethodsA study of 578 Chinese adolescents (46.9% males, mean age = 16.32 years, SD =0.54) was conducted using the Child and Adolescent Peer Relationship Inventory, Regulatory Emotional Self-Efficacy Scale, and the Adolescent Self-Injury Questionnaire.ResultsNegative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…The questionnaire has been used by past studies in measuring NSSI among Chinese adolescents and shows excellent reliability and validity in the populations. 70 In the present study, the Cronbach’s α of NSSI was 0.94.…”
Section: Methodssupporting
confidence: 45%
“…The questionnaire has been used by past studies in measuring NSSI among Chinese adolescents and shows excellent reliability and validity in the populations. 70 In the present study, the Cronbach’s α of NSSI was 0.94.…”
Section: Methodssupporting
confidence: 45%
“…After data collation, three or more articles on gender, age, residence, and whether they were solitary were investigated in the same form. The mean age of each study was 10 to 22 years, 13 to 18 years, 12 to 20 years, 13 to 20 years, and 13 to 25 years, and the number of subjects with NISS and non-NISS was 18/21, 93/19, 90/70, 90/139, and 230/130, and the NOS score was 6, 7, 6, 7, and 8 (Li, 2021a; Li, 2021b; Liu, 2020; Wen, 2020; Xu, 2021). The quality of the included studies was good, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16 articles entered the second stage of evaluation. After full-text reading, two articles older than 22 years, five articles including other mental disorders, and two articles due to other discrepancies were excluded, and five articles were finally included (Li, 2021a;Li, 2021b;Liu, 2020;Wen, 2020;Xu, 2021) (see Fig. 1).…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
See 2 more Smart Citations